Developing AI-Powered Chatbots for Mental Health Support - Shamshad Lakho,; Shaista Ashraf Farooqi,; Fatima Zafar ,; Saima Siraj , (Spectrum of Engineering Sciences, 2024)
As mental health challenges continue to rise globally, artificial intelligence (AI) powered chatbots are emerging as a promising solution to support mental health services, particularly by enhancing access to care and reducing the burden on mental health professionals. This study explores the development, efficacy, and impact of AI-driven chatbots for mental health support, focusing on their potential to provide timely interventions, deliver cognitive-behavioral therapy, and promote emotional well-being. Using a mixed-methods approach, this research evaluates user interaction with AI mental health chatbots, their perceived usefulness, and limitations. Results reveal that AI chatbots hold substantial promise in offering supplemental mental health support and increasing access to mental health resources, especially for underserved populations. However, ethical concerns and questions around data privacy, empathy, and efficacy persist, indicating the need for a balanced approach to AI implementation in mental health services. Future research should address these ethical dimensions while exploring ways to improve the efficacy of AI-driven mental health support. Keywords: AI-powered chatbots, mental health support, digital mental health, cognitive-behavioral therapy, artificial intelligence, mental health interventions, empathy in AI, data privacy in AI